Online social adaptation of first-year students and their academic performance. (October 2017) - Krasilnikov, Alexander; Smirnova, Anna
Abstract: This study investigates factors related to the social adaptation of first-year students. The sample consists of 68 students at a Russian university. The influences of the students' individual characteristics and basic social network indicators from the social networking siteVk.com on their grades were tested using ordinal logistic regression. A higher integration level at the beginning of the semester did not benefit students in terms of performance; however, in the middle of the semester, it was positively related to the students' grades. Individual characteristics, such as the city of origin and academic abilities, were also significant predictors of academic outcomes. Highlights: There was no relationship between the time spent online and the academic performance. Individual characteristics and the community involvement affect the adaptation. Students who continue their education in hometown tend to obtain higher scores. Active integration in the online community of fellow students leads to lower grades. Steady socialization in the first half of the semester positively affects grades.